Oligodendrocyte differentiation from human neural stem cells: A novel role for c-Src. (November 2018) - Wang, Le; Schlagal, Caitlin R.; Gao, Junling; Hao, Yan; Dunn, Tiffany J.; McGrath, Erica L.; Labastida, Javier Allende; Yu, Yongjia; Feng, Shi-qing; Liu, Shao-yu; Wu, Ping
Abstract: Human neural stem cells (hNSCs) can differentiate into an oligodendrocyte lineage to facilitate remyelination in patients. Molecular mechanisms underlying oligodendrocyte fate specification remains unknown, hindering the development of efficient methods to generate oligodendrocytes from hNSCs. We have found that Neurobasal-A medium (NB) is capable of inducing hNSCs to oligodendrocyte progenitor cells (OPCs). We identified several signaling molecules are altered after cultivation in NB medium, including Akt, ERK1/2 and c-Src. While sustained activation of Akt and ERK1/2 during both NB induction and subsequent differentiation was required for OPC differentiation, c-Src phosphorylation was increased temporally during the period of NB induction. Both pharmacological inhibition and RNA interference confirmed that a transient elevation of phospho-c-Src is critical for OPC induction. Furthermore, inactivation of c-Src inhibited phosphorylation of Akt and ERK1/2. In summary, we identified a novel and critical role of c-Src in guiding hNSC differentiation to an oligodendrocyte lineage. Graphical abstract: Highlights: Neurobasal-A medium allows for efficient differentiation of oligodendrocyte precursor cells. Transient activation of c-Src is critical for oligodendrocyte fate. Neurobasal-A medium induces sustained activation of Akt and ERK1/2.